Expression of Subtext in Literary Text - Qozoqova Nozima Abdulboqiyevna; Babaxanova Dilarom Axmatkhanovna; Tajibayeva Dilfuza Erkinovna (Zien Journals, 2023)
This article analyzes the linguistic basis of the expression of subtext in an literary text. It highlights the important aspects of subtext, such as irony, sarcasm, mockery
Keywords: subtext; speech situation; speaker; listener